Acceptance of Mobile Banking (MB) Framework in Pakistan – A Systematic Review - Hassan, Masood; Qureshi, Muhammad Azeem; Abbasi, Ahsan Naseer (JISR management and social sciences & economics, 2021)
Technological advancement is one of the key sources of competitive advantage for modern-day businesses. Specifically, IT-based innovations in financial services such as mobile banking (MB) have revolutionized banking practices. However, in developing countries like Pakistan with decrepit infrastructure and less education, mobile banking has gained less attention. This study, through a systematic literature review, aims to assess the key factor of mobile banking acceptance. An electronic search was carried out incorporating 11 databases of majorly publish multidisciplinary articles. The outcomes are limited to the country of Pakistan and restricted by the year. 12 articles were identified as relevant to this particular systematic review based on the identified keywords. All the information is extracted from every single research article to impart data for the research title, author, journal name, methodology/model, year, study purpose, and major findings. The findings of this study suggest that despite mobile banking is gaining a foothold in Pakistan, ease of use, privacy, security, reliability, lower risk are the key factors that affect acceptance of mobile banking among customers. This study has some strong practical implications for the banking industry.